O reflexo da presença de sementes esverdeadas na qualidade fisiológica em soja - Zorato, Maria de Fátima (2003)
Chlorophyll retention has been affecting soybean seed production, in the savannah (cerrado) region, mainly in the state of Mato Grosso. The consequence of this verification, are the losses in germination and vigor, and consequently losses in establishing an adequate plant population, at seeding. Chlorophyll decay can be affected by the maturation period, drying conditions, climatic conditions, and desiccating chemical agents. The maturation process, besides the importance of degradation from the green pigmentation, has a distinct effect on the production of specific germination enzymes, such as isocitrate lyase and malate syntase, these convert the lipids into soluble sugars. Maturation can also be considered important in reducing chlorophyll s capacity to produce free radicals that cause oxidation damage, these that determine the storage life of seed. Within stored seed, changes occur associated with deterioration, these can be measured through accelerated aging and biochemical reactions. This study was developed with the objective; verify the influence exerted on quality, evaluate adjuvant protocols in determining this quality of seed with chlorophyll retention. Green seed demonstrated lower germination, viability and vigor, less uniformity in seedlings, a higher rate of deterioration, higher level of leachate, reduced plant length, lower emergence capacity in the field, as well as a lower dry matter weight. Chlorophyll is an indication of reducion quality in soybean seeds. In the tetrazolium tests, the subclass WD 4-5, indicated the risk of the physiological quality of lot, when present, green seed. The viability obtained from a tetrazolium test, in substitution to accelerated aging germination test with an exposure of 24 hours can be utilized in determining the quality of green soyabena seeds.